Characterisation of titanium oxide layers using Raman spectroscopy and optical profilometry: Influence of oxide properties - Ekoi, E.J.; Gowen, A.; Dorrepaal, R.; Dowling, D.P. (Results in physics, 2019)
[Display omitted] This study evaluates the use of a combination of Raman spectroscopy and optical profilometry as a surface characterisation technique for the examination of oxide layers grown on titanium metal substrates. The titanium oxide layers with thickness of up to 8 µm, were obtained using a low-pressure oxygen microwave plasma treatment of the titanium metal substrate. The effect of the microwave plasma processing conditions (input power, pressure and treatment time) on the Raman bandwidth, intensity and peak position was evaluated. Also, the effect of these processing conditions on the surface roughness parameters (Sa, Sdq, Ssk and Sku) of the oxide layers was investigated. Analysis of the peak positions of Eg and A1g modes indicated that the effects of input power and chamber pressure was to induce a shift towards the lower frequency with increasing input power and pressure (1–2 kPa). The intensity of the Raman bands was found to be dependent on the morphology and surface chemistry of the oxide layer. The intensity of Raman band (A1g), was found to be particularly influenced by the average surface roughness (Sa) and the crystallite size. Exponential and polynomial relations were found to correlate with these properties. A two-latent variable Partial Least Squares Regression model developed on Raman spectral data could predict surface roughness with a coefficient of determination (R2) of approx. 0.87 when applied to the testing of an independent set of titanium oxide test coatings.